APLIKASI PROBIOTIK DENGAN KOSENTRASI YANG BERBEDATERHADAP PERTUMBUHAN UDANG VANNAMEI (Litopenaeus vannamei) - Burhanuddin Burhanuddin; Farhanah Wahyu; Suratman Suratman (Universitas Muhammadiyah Makassar, 2016)
The use of probiotics as an attempt to improve the cultivation environment and suppress the disease proved to help overcome some of the problems in shrimp farming. This study aims to determine the exact concentration of probiotics in shrimp maintenance Vanannamei and see the effects on water quality, growth, survival, and shrimp production Vannammei. Research carried out on a laboratory scale by using 12 aquariums measuring 30 x 25 cm with a volume of 25 liters each aquarium filled sized shrimp with stocking density 20 birds. Probiotics mixed premises of feed and given 4 times a day with a concentration corresponding treatments, A = 3 PPM, B = 4 PPM, C = 5 PPM and D controls that are set in a completely randomized design (CRD) with 4 treatments and 3 replications. During maintenance of shrimp fed as much as 5% of the total biomass with a frequency of 4 times/day, the results of research addressing that administration of probiotics with different concentrations significantly affected the growth and survival of Shrimp Vannamae although not significantly affect water quality.